The pursuit of evidence-based practice: Comparisons of three guidelines on psychosocial interventions for alcohol problems. Issue 3 (June 2014) - Bergmark, Anders; Skogens, Lisa; Von Greiff, Ninive
Aims: In this article we scrutinise three prominent guidelines on psychosocial interventions for alcohol problems. We pay special attention to how congruent the guidelines are in terms of the interventions recommended, and the processes used in order to identify and rank the "evidence" underpinning these recommendations. Data: The analysed guidelines are: 1) Practice Guideline for the Treatment of Patients with Substance Use Disorders, American Psychiatric Association (2006); 2) Alcohol-Use Disorders. The NICE Guideline on Diagnosis, Assessment and Management of Harmful Drinking and Alcohol Dependence (2011), National Collaborating Centre for Mental Health, UK; 3) Guidelines for the Treatment of Alcohol Problems, Australian Government, Department of Health and Ageing (2009). The purpose is not to review the three guidelines as such, but to study them as an example of the production of evidence. All report to be based on "best available evidence", so the guidelines were compared both regarding the actual recommendations and the guideline production procedures and differences in these procedures with related consequences. Results & CONCLUSIONS: Prestigious organisations in different national contexts have reached divergent conclusions about evidence-based practice and the quality of the scientific studies underpinning these conclusions. Differences in the guidelines regarding interpretations, limitations and grading illustrate the difficulties with the dilemmas of sensitivity (to include factors that are significant for how a psychological intervention is to be judged) and specificity (that irrelevant studies are cleared off) in the recommendations presented.